(untitled) (UNED Research Journal, 2019)
Introduction: Mentha spicata, commonly known as spearmint, is the most common and popular cultivated mint, and is used in food, perfumes and pharmaceutical products. Objective: To determine the yield, composition and properties of essential oil from M. spicata grown in Santiago del Estero, Argentina. Methods: We used steam distillation, gas chromatography and mass spectrometry to determine chemical composition, antioxidant activity and acetylcholinesterase inhibition. Results: Essential oil yield ranged from 0.8 to 1.3 mL·100 g-1 DM. The main essential components were carvone (60,72-68,09%), limonene (14,23-16,41%), α-pinene (0,12-3,14%), β-myrcene (0,35-2,33%), 1,8-cineole (1,69-2,73%), cis-dihydrocarvone (1,82-2,31%), trans-craveol (1,09-1,19%), β-bourbonene (2,44-3,17%) and β-Caryophyllene (1,42-1,82%). The oil had high antioxidant activity, with IC50 values among 7,5-12,06 µg/mL (DPPH method) and 26,94-38,14 µg/mL (β-carotene/linoleic acid method). It had good inhibition of acetylcholisterenase, with enzyme inhibition zones of 0,4-0,9 cm. Conclusion: The yield, quality and properties of the essential oil from M. spicata grown in Santiago del Estero meet market requirements.